Sources of Capital for Traditional Market Traders in Pertamina Market: Analysis of Financing Strategies and Business Capital Management - Nur Arisah; Ika Wisudawaty (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to determine the sources of capital for traditional market traders in Pertamina Market and delve into financing strategies and business capital management with the aim of understanding the crucial role of capital sources in supporting the business continuity of traders and identifying effective and efficient financial management practices. A qualitative descriptive method is used in this study by collecting data through focused and in-depth interviews with Pertamina Market traders. The research was conducted at Pertamina Market, Tamalanrea Village, Bontotiro District, Bulukumba Regency which was conducted on July 4-11, 2024 by interviewing 7 Pertamina Market traders in accordance with the business fields in Pertamina Market to listen directly to traders' views, experiences, and preferences regarding their sources of capital. Research that has been conducted shows that traditional market traders in Pertamina Market take advantage of various sources of capital, such as personal funds, bank loans, and assistance from family or friends. They showed foresight in financing strategies and adaptability in managing business finances. Diversifying capital sources and awareness of the importance of capital management help traders reduce risk, increase financial flexibility, and achieve long-term success.